Using Stochastic SIS Epidemic Model with Markovian Environment for Infectious Diseases - Musbah, Raga; Elnajar, Khadiga (Libyan Journal of Science &Technology, 2022)
There are various types of stochastic epidemic models that can be formulated to deal with different types of diseases. In this project (SIS) epidemic model Susceptible - Infected- Susceptible will be considered relating to the Continuous Time Markov chains process. Each type of the epidemic models studies the disease according to its status. In particular, the SIS epidemic model regards infectious diseases. The Maple code is provided in this project, which is created to produce and predict the number of infected individuals and the disease prevalence at a fixed time.